The effect of level substitution of tapioca flour with local indonesian tuber flour on the physicochemical quality of local chicken sausage - Muhammad Mar'ie Sirajuddin; Putra, Azchar P. P. (Fakultas Peternakan Universitas Papua, 2025)
This study aimed to evaluate the effect of substituting tapioca flour with local Indonesian tuber flours on the physicochemical quality of chicken sausages. Three types of tuber flours—Cilembu sweet potato, purple sweet potato, and yellow sweet potato—were used as partial substitutes for tapioca flour. Four formulations were prepared: T0 (20 g tapioca, control), T1 (12 g tapioca + 2 g Cilembu + 2 g purple sweet potato + 4 g yellow sweet potato), T3 (12 g tapioca + 4 g Cilembu + 2 g purple sweet potato + 2 g yellow sweet potato), and T4 (12 g tapioca + 2 g Cilembu + 4 g purple sweet potato + 2 g yellow sweet potato). Physicochemical parameters assessed included pH, water-holding capacity (WHC), tenderness, cooking loss, and proximate composition (moisture, protein, fat, ash, and carbohydrate). The results showed that tuber flour substitution had a significant effect (P<0.05) on both chemical and physical qualities of chicken sausages. Treatment T3 exhibited the most favorable results, with higher protein and ash contents, lower fat levels, and improved WHC and tenderness compared to the control. These outcomes indicate that tuber flours not only act as effective functional fillers but also enhance the nutritional and technological qualities of chicken sausages. In conclusion, the partial substitution of tapioca with local Indonesian tuber flours offers a promising strategy to develop healthier and more functional meat products. This approach also supports the valorization of indigenous crops, contributing to food diversification and the utilization of local agricultural resources in Indonesia.